Manual and automated tissue segmentation confirm the impact of thalamus atrophy on cognition in multiple sclerosis: A multicenter study - Burggraaff, Jessica; Liu, Yao; Prieto, Juan C.; Simoes, Jorge; de Sitter, Alexandra; Ruggieri, Serena; Brouwer, Iman; Lissenberg-Witte, Birgit I.; Rocca, Mara A.; Valsasina, Paola; Ropele, Stefan; Gasperini, Claudio; et al. (NeuroImage clinical, 2021)
•Thalamus atrophy is associated with cognitive impairment in multiple sclerosis.•This was confirmed by automated and manual segmentations, but effect sizes varied.•The algorithms work in a multi-center setting.•Automated techniques exhibit proportional bias with respect to thalamus size.•Differences between vendors can affect the robustness of these associations. Thalamus atrophy has been linked to cognitive decline in multiple sclerosis (MS) using various segmentation methods. We investigated the consistency of the association between thalamus volume and cognition in MS for two common automated segmentation approaches, as well as fully manual outlining. Standardized neuropsychological assessment and 3-Tesla 3D-T1-weighted brain MRI were collected (multi-center) from 57 MS patients and 17 healthy controls. Thalamus segmentations were generated manually and using five automated methods. Agreement between the algorithms and manual outlines was assessed with Bland-Altman plots; linear regression assessed the presence of proportional bias. The effect of segmentation method on the separation of cognitively impaired (CI) and preserved (CP) patients was investigated through Generalized Estimating Equations; associations with cognitive measures were investigated using linear mixed models, for each method and vendor. In smaller thalami, automated methods systematically overestimated volumes compared to manual segmentations [ρ=(-0.42)-(-0.76); p-values < 0.001). All methods significantly distinguished CI from CP MS patients, except manual outlines of the left thalamus (p = 0.23). Poorer global neuropsychological test performance was significantly associated with smaller thalamus volumes bilaterally using all methods. Vendor significantly affected the findings. Automated and manual thalamus segmentation consistently demonstrated an association between thalamus atrophy and cognitive impairment in MS. However, a proportional bias in smaller thalami and choice of MRI acquisition system might impact the effect size of these findings.